Kilka uwag na temat planowania strategicznego w małym przedsiębiorstwie - Nogalski, Bogdan; Walentynowicz, Piotr; Szpitter, Agnieszka (Some suggestions about the subject of strategic planning in a small enterprise, 2006)
Lately we have been observing the increasing role and importance of small enterprises for the economy of Poland. Conditions of their functioning are increasingly demanding, therefore the need intensities to increase the level of professionalism in managing the SMEs. Application of strategic management increases the probability of growth and development of a contemporary enterprise. Therefore instruments of strategic management can be used not only to develop large and medium--sized, but also - as it is shown in this paper - small enterprises. Special attention was put to the procedure of strategy planning, and the recommended methods of strategic analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 121-131